2017
DOI: 10.1177/1524839917716931
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Behaviors and Outcomes Among School-Based Employees in a Wellness Program

Abstract: School employees may benefit from a comprehensive worksite wellness program, particularly to improve health behaviors. However, mental health and job-related outcome results were mixed over 2 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…1 This presents employers with a unique opportunity to reach a large segment of the population that otherwise may not be exposed to, or engaged in, organized health improvement efforts. Over 30 years of research suggests that comprehensive, well-designed, well-executed, and properly evaluated workplace health promotion (WHP) programs can lead to reductions in healthcare utilization and costs 2,3 ; enhance work performance 4 ; improve employee health and well-being factors 5 such as job stress, 6 sleep, 7 physical activity and nutrition 8 ; impact value-on-investment metrics such as job satisfaction and quality of work 9 ; and, in some cases, may offer positive business results such as bolstering stock market performance 1012 and a positive return-on-investment (ROI). 13–16…”
mentioning
confidence: 99%
“…1 This presents employers with a unique opportunity to reach a large segment of the population that otherwise may not be exposed to, or engaged in, organized health improvement efforts. Over 30 years of research suggests that comprehensive, well-designed, well-executed, and properly evaluated workplace health promotion (WHP) programs can lead to reductions in healthcare utilization and costs 2,3 ; enhance work performance 4 ; improve employee health and well-being factors 5 such as job stress, 6 sleep, 7 physical activity and nutrition 8 ; impact value-on-investment metrics such as job satisfaction and quality of work 9 ; and, in some cases, may offer positive business results such as bolstering stock market performance 1012 and a positive return-on-investment (ROI). 13–16…”
mentioning
confidence: 99%
“…A valuable benefit of the health campaigns presented in this paper is that they provide opportunities for employees to improve their health, which can improve worker productivity and combat more serious and costly health problems in the future. Previous studies have shown that the selected campaigns presented in this study improve health and lower healthcare expenditures ( Merrill and LeCheminant, 2016 ; LeCheminant et al, 2017 ; LeCheminant et al, 2015 ; Merrill and Sloan, 2014 ). Completion of one or more health campaign was associated with a lower mean number of pharmacy claims.…”
Section: Discussionmentioning
confidence: 90%
“…The results of the study showed that cost of medical claims was lower, but frequency of claims was higher among participants. Other research has shown that the program has improved health behaviors and health risks ( LeCheminant et al, 2017 ; LeCheminant et al, 2015 ; Merrill and Sloan, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…This finding differs from some existing literature. Although some WW interventions aim to increase awareness of health and wellness to initiate behavior change (LeCheminant et al, 2017), few studies measure or report on change in awareness levels. A 5-year WW intervention outside of ECE settings that aimed to improve the health and well-being of employees found no significant improvement in knowledge/awareness around physical activity and diet (Blake, Zhou, & Batt, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In elementary school settings, the implementation of workplace wellness (WW) programs has been associated with positive outcomes. For example, a comprehensive 2-year WW program in a large public school district significantly improved several health outcomes in staff, including increased days and minutes of physical activity, fruit and vegetable consumption, and restful sleep (LeCheminant, Merrill, & Masterson, 2017). This study suggests that WW programs can be successful in school-based settings, which are likely to translate to preschool centers.…”
Section: Introductionmentioning
confidence: 99%